2012
DOI: 10.1007/s12053-012-9163-9
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking energy use in the paper industry: a benchmarking study on process unit level

Abstract: There are large differences between paper mills in, e.g. feedstock use and grades produced, but typical processes are similar in all mills. The aim of this study is to benchmark the specific energy consumption (SEC) of similar processes within different paper mills in order to identify energy improvement potentials at process level. We have defined improvement potentials as measures that can be taken at mill/ process level under assumed fixed inputs and outputs. We were able to use industrial data on detailed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 18 publications
1
54
0
Order By: Relevance
“…Another explanation could be that the saving of energy in the PPI has historically mostly been done by engineers and/or technicians since an in-depth holistic understanding of the causes and effects of various processes and technologies is needed to do so, and therefore the technical personnel do what they are meant to do-save energy via technology and engineering. This explanation is supported by the results of research conducted for paper mills, which emphasized the importance of a decent understanding of the processes, since without such understanding even a detailed benchmarking of processes may not lead to accurate estimations of energy improvement potentials [19].…”
Section: The Perception Of What Energy Management In the Ppi Ismentioning
confidence: 86%
See 3 more Smart Citations
“…Another explanation could be that the saving of energy in the PPI has historically mostly been done by engineers and/or technicians since an in-depth holistic understanding of the causes and effects of various processes and technologies is needed to do so, and therefore the technical personnel do what they are meant to do-save energy via technology and engineering. This explanation is supported by the results of research conducted for paper mills, which emphasized the importance of a decent understanding of the processes, since without such understanding even a detailed benchmarking of processes may not lead to accurate estimations of energy improvement potentials [19].…”
Section: The Perception Of What Energy Management In the Ppi Ismentioning
confidence: 86%
“…Moreover, the results showed that large amounts of heat, especially in the evaporation plant, could be saved. Another example is the benchmarking of similar processes at a detailed process level by comparing SEC in 23 different Dutch paper mills [19]. The benchmarking identified that 15% of the total primary energy use could be saved by improving EE in the drying, wire, and press sections [19].…”
Section: Benchmarkingmentioning
confidence: 99%
See 2 more Smart Citations
“…Under the social background of increasingly serious environmental problems and more nervous resource energy, as the basic industry of national economy, the papermaking have to meet the market demand as well as save resource and energy as the starting point (Jung & Kutzner, 1978;Lamberg, Ojala, Peltoniemi, & Särkkä, 2012;Laurijssen, Faaij, & Worrell, 2013;Nickels, 1988;Torres, Lenon, Craperi, Wilting, & Blanco, 2011;Wainwright, 1999;Zhou & Shi, 2011). As a major environmental pollution, papermaking industry as early as 2005, was listed in the circular economy pilot, to formally carry out the circular economy model, while Germany, Japan, the United States, and other developed countries vigorously promoted clearer production technology of papermaking.…”
Section: Introductionmentioning
confidence: 99%